2017
DOI: 10.1080/15582159.2017.1286210
|View full text |Cite
|
Sign up to set email alerts
|

“No Excuses” Charter Schools: A Meta-Analysis of the Experimental Evidence on Student Achievement

Abstract: While charter schools differ widely in philosophy and pedagogical views, the United States's most famous urban charter schools typically use the No Excuses approach. Enrolling mainly poor and minority students, these schools feature high academic standards, strict disciplinary codes, extended instructional time, and targeted supports for low-performing students. The strenuous and regimented style is controversial amongst some scholars, but others contend that the No Excuses approach is needed to rapidly close … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 50 publications
4
45
0
1
Order By: Relevance
“…The no-excuses (NE) pedagogical model has become the most prominent and fastest growing educational alternative for urban youth in the United States in the past 20 years, and is expected to keep expanding in the United States and beyond (Cheng et al, 2015). The main goal guiding these schools is to close the pernicious achievement gap and to increase college completion rates among the schools’ disadvantaged populations.…”
Section: Introductionmentioning
confidence: 99%
“…The no-excuses (NE) pedagogical model has become the most prominent and fastest growing educational alternative for urban youth in the United States in the past 20 years, and is expected to keep expanding in the United States and beyond (Cheng et al, 2015). The main goal guiding these schools is to close the pernicious achievement gap and to increase college completion rates among the schools’ disadvantaged populations.…”
Section: Introductionmentioning
confidence: 99%
“…Success and achievement are measured through student growth on frequent assessments, and indeed natural experiments (i.e., lottery-based studies) have found that urban charter schools subscribing to the “no excuses” model have shown positive and statistically significant impacts on standardized test scores (Angrist et al, 2013; Cohodes, 2018). A recent meta-analysis estimates that “no excuses” charter schools increase student math and literacy achievement by 0.25 and 0.17 standard deviations, respectively, compared to students in traditional public schools, for each year of attendance (Cheng et al, 2017). Such findings are likely responsible in part for the expansion of “no excuses” schools through millions of dollars in corporate and federal grants, though there is no evidence to suggest that it is the disciplinary policies and practices of these schools that lead to increases in academic achievement (Dobbie and Fryer, 2013; Torres and Golann, 2018).…”
mentioning
confidence: 99%
“…However, it is also dishonest to compare poor instructivist teaching with idealised constructivist teaching, the apparent fallacy underlying the argument that the underachievement of learners in South African low-quintile schools results from the prevalence of instructivist, and the absence of constructivist pedagogy. Such a view is clearly fallacious given evidence of high achievement associated with skilful instructivist pedagogy in the South African low-quintile context (Christie, Butler, & Potterton, 2007;Jansen & Blank, 2014;Malcolm, Keane, Hoohlo, Kgaka, & Ovens, 2000), as well as in other contexts, such as the highly instructivist Knowledge is Power Program (KIPP) schools in the USA (Cheng, Hitt, Kisida, & Mills, 2017).…”
Section: Learning Models and Associated Pedagogymentioning
confidence: 99%